Enhancing farmer's digital agency & co-creation- The FarMoRe experience in Vietnam - Vu, Trang (2025)
Presented by Trang Vu, International Rice Research Institute, at the “Increasing farmer’s digital agency for agroecology” webinar on 8 May 2025, an event of the Transformative Partnership Platform (TPP) for Agroecology and Agroecological TRANSITIONS Project (ATDT).